Bioremediation Potential of Nymphaea sp., Zantedeschia aethiopica, and Spirodela polyrhiza for Laundry Wastewater Treatment - Ramadhani, Abidah Bunga; Fadhilah, Eksa Adhwa; Lestari, Emilia Mia; Azizah, Hilda Nur; Christofan, Vinno Bayu; Surakusumah, Wahyu; Dewina, Restu Utari (Universitas Pendidikan Indonesia and Konsorsium Biologi Indonesia, 2024)
This research aims to assess the efficacy of three distinct types of aquatic plants, namely Nymphaea sp., Hydrocotyle sp., and Spirodela sp., in wastewater bioremediation from the laundry industry. The wastewater from the laundry industry contains a range of chemical substances that have the potential to pollute the surrounding environment. These include detergents, fragrances, and other chemicals that can cause pollution of the aquatic environment. The research method entailed the simultaneous planting of the three types of aquatic plants in controlled containers with the tested laundry wastewater. The temperature, pH, total dissolved solids (TDS), and dissolved oxygen (DO) of the laundry water effluent were measured before and after passing through the aquatic plant system. The results demonstrated that all three types of aquatic plants exhibited the capacity to reduce the concentration of TDS in laundry wastewater. The study revealed that there were notable differences in the effectiveness of various aquatic plant species in reducing TDS. Of the three plant species examined, Spirodela sp. demonstrated the greatest potential for reducing detergent concentrations, as indicated by a notable decrease in TDS.